2019
DOI: 10.1136/bmjopen-2018-028646
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with elevated consumption of alcohol in older adults—comparison between China and Norway: the CLHLS and the HUNT Study

Abstract: ObjectivesThe primary objective was to investigate the prevalence and factors associated with elevated alcohol consumption among older adults 65 years and above in China and Norway. The secondary objective was to compare the prevalence and factors in the two countries.DesignA secondary data analysis was conducted using two large cross-sectional studies (Chinese Longitudinal Healthy Longevity Survey data in 2008–2009 and Nord-Trøndelag Health Study data in 2006–2008).ParticipantsA total of 3223 (weighted) Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 88 publications
4
11
0
3
Order By: Relevance
“…The prevalence of reported elevated alcohol consumption was considerably high in older psychiatry patients and higher compared to what is reported in Norwegian population-based studies (Li et al, 2019;Tevik et al, 2017). However, the prevalence in the present study (27%) was in line with the prevalence found in a previous Norwegian study (23%), including comparable patients (Johannessen, Engedal, Larsen et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The prevalence of reported elevated alcohol consumption was considerably high in older psychiatry patients and higher compared to what is reported in Norwegian population-based studies (Li et al, 2019;Tevik et al, 2017). However, the prevalence in the present study (27%) was in line with the prevalence found in a previous Norwegian study (23%), including comparable patients (Johannessen, Engedal, Larsen et al, 2017).…”
Section: Discussionsupporting
confidence: 80%
“…In this context, there is also a gender perspective, but women today have moved more towards men's patterns of drinking (Bratberg et al, 2016). Lastly, regular, frequent and elevated alcohol consumption are in general found to be associated with a higher level of education (Johannessen, Engedal, Larsen, Stelander, & Helvik, 2017;Li, Wu, Selbaek, Krokstad, & Helvik, 2017;Li, Wu, Tevik, Krokstad, & Helvik, 2019;Tevik et al, 2019).…”
mentioning
confidence: 99%
“…A possible explanation for this association between educational status and alcohol consumption has previously been provided by Li et al [17]: in western societies, educational status correlates with socioeconomic status and older, higher educated people are more likely to afford alcohol and to engage in social drinking. Furthermore, this association was also reported in a recent survey among more than 5,000 Norwegian adults, where higher education attainment as well as being of a younger age were found to be positively associated with alcohol-related work-impairment [53].…”
Section: Discussionmentioning
confidence: 84%
“…It is known from previous studies that individual alcohol consumption patterns are influenced by specific factors, including socio-economic, socio-demographic, biographical characteristics (e.g. stressful life events) and personality traits [3,[14][15][16][17]. However, research on potential risk factors for alcohol consumption within the elderly population is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the mere ease of remembering less consumption, there may be other explanations for why agreement is higher when there is little consumption. For instance, restraint in alcohol consumption can be traced to a host of cultural (Dawson et al, 1995;Galvan & Caetano, 2003;Li et al, 2019;Livingston et al, 2020, p. 11;Vedøy & Amundsen, 2008) and health-related factors (Fillmore et al, 2007;Hassing, 2018;Stockwell et al, 2016;Tevik et al, 2019aTevik et al, , 2019b, which a next of kin is likely aware of. Another noteworthy finding is that agreement was higher for the category '4-7 times a week' than for all other categories except the category 'Not at all last year or ever' .…”
Section: Discussionmentioning
confidence: 99%